Role of murE in the Expression of β-Lactam Antibiotic Resistance in Staphylococcus aureus - Gardete, S. (American Society for Microbiology, 2004)
It was shown earlier that Tn551 inserted into the C-terminal region of murE of parental methicillin-resistant Staphylococcus aureus strain COL causes a drastic reduction in methicillin resistance, accompanied by accumulation of UDP-MurNAc dipeptide in the cell wall precursor pool and incorporation of these abnormal muropeptides into the peptidoglycan of the mutant. Methicillin resistance was recovered in a suppressor mutant. The murE gene of the same strain was then put under the control of the isopropyl-β-d-thiogalactopyranoside (IPTG)-inducible promoter P(spac). Bacteria grown in the presence of suboptimal concentrations of IPTG accumulated UDP-MurNAc dipeptide in the cell wall precursor pool. Both growth rates and methicillin resistance levels (but not resistance to other antibiotics) were a function of the IPTG concentration. Northern analysis showed a gradual increase in the transcription of murE and also in the transcription of pbpB and mecA, parallel with the increasing concentrations of IPTG in the medium. A similar increase in the transcription of pbpB and mecA, the structural genes of penicillin-binding protein 2 (PBP2) and PBP2A, was also detected in the suppressor mutant. The expression of these two proteins, which are known to play critical roles in the mechanism of staphylococcal methicillin resistance, appears to be—directly or indirectly—under the control of the murE gene. Our data suggest that the drastic reduction of the methicillin MIC seen in the murE mutant may be caused by the insufficient cellular amounts of these two PBPs.